Pyrrole as an Important Scaffold of Anticancer Drugs: Recent Advances - Emilio Mateev; Maya Georgieva; Alexander Zlatkov (Frontiers Media S.A., 2022)
With the significant increase of patients suffering from different types of cancer, it is evident that prompt measures in the development of novel and effective agents need to be taken. Pyrrole moiety has been found in various active compounds with anti-inflammatory, antiseptic, antibacterial, lipid-lowering and anticancer properties. Recent advances in the exploration of highly active and selective cytotoxic structures containing pyrrole motifs have shown promising data for future investigations. Accordingly, this review presents an overview of recent developments in the pyrrole derivatives as anticancer agents, with a main focus towards the key moieties required for the anti-tumor activities. Pyrrole molecules comprising prominent targeting capacities against microtubule polymerization, tyrosine kinases, cytochrome p450 family 1, histone deacetylase and bcl-2 proteins were reported. In addition, several mechanisms of action, such as apoptosis, cell cycle arrest, inhibiting kinases, angiogenesis, disruption of cell migration, modulation of nuclear receptor responsiveness and others were analyzed. Furthermore, in most of the discussed cases we provided synthesis schemes of the mentioned molecules. Overall, the utilization of pyrrole scaffold for the design and synthesis of novel anticancer drugs could be a promising approach for future investigations.